1996
DOI: 10.1111/j.1600-079x.1996.tb00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ganglion cell activity in the pineal gland of the rainbow trout: Effects of cholinergic, catecholaminergic, and GAB Aergic receptor agonists

Abstract: Second order neurons within intact isolated pineal glands of the rainbow trout were explored by extracellular recordings to investigate modulatory effects of putative intrapineal neurotransmitters. Acetylcholine, dopamine, and norepinephrine were found to increase ganglion cell activity in a majority of cells tested. The excitatory effects of acetylcholine, dopamine, and norepinephrine were mimicked by muscarinic, dopamine D2, and beta-adrenergic receptor agonists and significantly increased with the applied l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, ChAT-ir nonganglionic cells have been reported in the pineal organ of Phoxinus (Ekström and Korf, 1986) and ChAT-ir photoreceptors in the pineal organ of lampreys and elasmobranchs (Pombal et al, 1997(Pombal et al, , 1999bAnadón et al, 2000). Studies carried out in salmonids have revealed the presence of acetylcholine receptors in this organ (Samejima et al, 1994) and have demonstrated that ACh causes changes in the activity of ganglion cells (Brandstä tter et al, 1995;Brandstä tter and Hermann, 1996). If a cholinergic network is present in the pineal organ of trout, it was undetectable by present immunocytochemical techniques.…”
Section: Diencephalon and Pretectummentioning
confidence: 99%
“…However, ChAT-ir nonganglionic cells have been reported in the pineal organ of Phoxinus (Ekström and Korf, 1986) and ChAT-ir photoreceptors in the pineal organ of lampreys and elasmobranchs (Pombal et al, 1997(Pombal et al, , 1999bAnadón et al, 2000). Studies carried out in salmonids have revealed the presence of acetylcholine receptors in this organ (Samejima et al, 1994) and have demonstrated that ACh causes changes in the activity of ganglion cells (Brandstä tter et al, 1995;Brandstä tter and Hermann, 1996). If a cholinergic network is present in the pineal organ of trout, it was undetectable by present immunocytochemical techniques.…”
Section: Diencephalon and Pretectummentioning
confidence: 99%
“…The cholinergic (both muscarinic and nicotinic), adrenergic as well as dopaminergic receptors were detected in the rainbow trout pineal , in which the density of muscarinic receptors was two‐fold higher than the nicotinic receptors (Samejima et al. 1994) and the catecholamine receptors were located pre‐synaptically to pineal ganglion cells (Brandstätter and Hermann 1996). However, the relative role of different neuronal signals in the regulation of photo‐induced expression of photoreceptor proteins in the pineal remained unknown for any fish species.…”
mentioning
confidence: 99%
“…Since acetylcholine is a potent modulator of pineal cell activity in lower vertebrates, particularly fishes [39, 40], the presence of a cholinergic system within the pineal gland could be a phylogenetically conservative feature of this neuroendocrine organ. Data obtained by different laboratories on the role of acetylcholine in modulating melatonin production are not consistent [22, 32, 41, 42]and whether muscarinic and/or nicotinic receptors participate in the various effects of acetylcholine is still contradictory [35, 36, 43, 44].…”
Section: Introductionmentioning
confidence: 99%